Avatars cervantins d’un stéréotype : le « récit de tempête » et le brouillage des frontières textuelles dans Los trabajos de Persiles y Sigismunda - Michel Moner (Les Cahiers de Framespa)
The presence of storm scenes, abundantly documented in their forerunners in homeric and biblical literature, is an occasion of defining their status in the context of romantic texts in which they appear under a mixed narrative/descriptive form. The singular use they are put to in Cervantes’ Persiles through a sophisticated device of frontier blurring betwen textual categories, brings to light the hidden potential of such «mini-narratives», seen as stereotypes ever since classical times.